The connectivity between damage to physical infrastructure and social science: a new field study protocol concept - Clapp, Todd, author; van de Lindt, John, advisor; Mahmoud, Hussam, committee member; Peek, Lori, committee member; McAllister, Therese, committee member (Colorado State University. Libraries, 2016)
The primary objective of this thesis is to introduce a field study methodology that will be calibrated over the next several years to enable researchers to collect data in the field that can be used to better understand and quantify community resilience. Specifically, a key objective is to provide a mechanism to link damage to the physical infrastructure to social and economic dimensions of a community in a measurable way. Although there have been several past attempts at creating a common post-disaster field study protocol, none of them have attempted to quantify community resilience in a quantitative manner that can be used for risk and resilience analysis. The methodology explained in this thesis is unique because it discusses potential metrics that can be used to quantify community resilience and describes methods of quantifying these metrics using field data. These metrics come from a combination of disciplines including engineering, sociology, and economics. This work combines a literature review of past field study protocols with perceived data requirements in order to outline a field study methodology that can be used for disasters (primarily natural; not anthropogenic) of any type including tornados, hurricanes, flood, tsunamis, wildland-urban interface (WUI) fires, and earthquakes. Algorithms were derived that include the ability to process raw field study data in order to create probabilistic models of resilience metrics (i.e., fragility functions). These algorithms were then demonstrated using existing field data related to population dislocation caused by Hurricane Andrew. Finally, a community resilience field study was conducted five years into the recovery process in order to investigate and model the long term effects of the May 22, 2011 tornado that occurred in Joplin, MO. The planning and execution of this study is described and the data that was gathered is used to provide an illustrative example of the interconnectivity between the physical damage and socio-economic consequences.
Keywords: disaster; engineering; sociology; economics; community resilience; field studies